Methylene blue test and adsorption capacity of clays - Tereza Plaček Otcovská; Barbora Mužíková; Pavel Padevět (Acta Polytechnica CTU Proceedings, 2022)
This article presents results of experimental measurements focused on an ability of clay to adsorb Methylene Blue dye. This adsorption capacity is determined by a methylene blue test. Adsorption capacity could be a specific characteristics of individual types of clay which are basic component of earth. Therefore, the methylene blue test could be a good method to identify the composition of an unknown earth. Composition of earth is very important for example for final properties of unfired earth structures. The basic common element in all experiments was at least one of the elementary clay minerals (montmorillonite, kaolinite, illite). In the case of adsorption ability measurements, it was determined what is the maximum ability of a given clay to adsorb the Methylene Blue dye. The highest adsorption capacity was determined for montmorillonite clay, lower for kaolinite clay and the lowest for illite clay.